Navigating Soil Erosion Challenges in Malaysia: Insights, Prospects, and Solutions - Chin, Edenver; Maharjan, Rabin; Emalya, Nikita (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2023)
The escalating global demand for forest products, driven by economic growth and a growing population, has led to increased forest conversion activities. Forest conversion involves transforming forested areas to meet industrial demands, resulting in severe ecological consequences. This review focuses on the state of soil erosion practices in Malaysia, which is a pressing issue with wide-ranging impacts on soil health, agricultural sustainability, and the environment. Malaysia's geographical location exposes it to the El Nino phenomenon, characterized by disrupted climate patterns and altered rainfall intensities, indirectly contributing to soil erosion. During El Nino events, diminished vegetation cover, primarily due to rainfall deficits, increases soil susceptibility to erosion, emphasizing the need for adaptive erosion control measures. Soil erosion poses a significant challenge to the sustainability of agriculture and terrestrial ecosystems. Malaysia has made efforts to address this issue by implementing soil and water conservation practices like terraces, grassed waterways, strip cropping, and conservation tillage, which effectively reduce erosion rates. However, these methods face challenges due to the variations in natural erosion rates driven by extreme events. Additionally, the conversion of natural forests to economic forests remains an underexplored concern in Malaysia, hindering the development of tailored soil erosion control strategies. Addressing soil erosion demands a comprehensive approach that includes research, policy support, and empowering farmers to adopt soil conservation practices. Soil erosion affects ecosystems, water resources, and urban development, necessitating multifaceted solutions to preserve both environmental sustainability and agricultural productivity in the face of evolving environmental challenges.